A possible conceptualization of the information systems (IS) artifact: A general systems theory perspective. (28th December 2020) - Chatterjee, Sutirtha; Sarker, Suprateek; Lee, Michael J.; Xiao, Xiao; Elbanna, Amany
Abstract: This opinion paper addresses and contributes to the discourse on whether there is a central artifact that captures the essence of the information systems (IS) discipline. It argues that the IS discipline can, and should be, faithfully captured by an IS artifact. We offer a theoretical conception of the IS artifact by drawing upon General Systems Theory (GST). Key concepts of GST are distilled as meta‐principles which inform our formulation of the IS artifact. We use the meta‐principles of the IS artifact to develop salient assertions that theorize what an 'IS' is. To demonstrate the appropriateness of our conception, we illustrate how the assertions we developed are consistent with patterns related to emerging topics in IS research, notably, healthcare and IT, and Fintech. We formulate a research agenda on these emerging topics—based upon the conceptions developed in the paper—to guide future research. We conclude with the contributions and implications of our study, including the relevance for IT‐enabled work in the era of the COVID‐19 pandemic.